A study on prevalence of diabetes mellitus among adult tuberculosis patients in tertiary health care centre, Hyderabad - Laxmi, S.Bhavana; Kandikonda, Sri Harsha; Vemuri, Jyothi Lakshmi Naga; Rao, R. L. Lakshman (International Journal Of Community Medicine And Public Health, 2019)
Background: Tuberculosis is a major public health problem and is among top ten causes of deaths worldwide. People with diabetes are three times at higher risk of getting infected with tuberculosis. Globally 10.4 million TB cases exists of them 10% are linked to diabetes. In India 13% of Tuberculosis cases were diabetic. DM has been reported to modify the clinical features of TB. The objectives were to study the prevalence of diabetes mellitus among adult tuberculosis patients registered in DOTS centre in tertiary health care centre, Hyderabad and to study the clinical profile of tuberculosis in study subjects. Methods: A cross sectional study was conducted in 4 DOTS centres under tertiary health care facility, Hyderabad. Sample size 200 was calculated using formula 4PQ/L2. Study subjects were registered adult tuberculosis patients attending DOTS centre and undergoing anti tuberculosis treatment. Data from study subjects was obtained by interview method using semi structured questionnaire consisting of socio-demographic parameters and clinical parameters. Results: Out of 200 patients, the prevalence of DM was found to be 18% (n=36). Increasing age (p<0.000), male sex (p=0.04), low BMI (p=0.02), family history of TB (p=0.017), Sputum positive severity (p=0.0008) are significantly associated with DM-TB comorbidity and clinical manifestations like bilateral involvement (p=0.151), multi lobes (p=0.243), other associated lung diseases (p=0.154), treatment category (p=0.8203) are not significantly associated with DM-TB comorbidity. Conclusions: Bidirectional screening of TB and DM will detect early and prevent complications of comorbiditiy.